The Biological Activity Mechanism of Chlorogenic Acid and Its Applications in Food Industry: A Review - Wang, Liang; Pan, Xiaoqi; Jiang, Lishi; Chu, Yu; Gao, Song; Jiang, Xingyue; Zhang, Yuhui; Chen, Yan; Luo, Shajie; Peng, Cheng (Frontiers in Nutrition, 2022)
Chlorogenic acid (CGA), also known as coffee tannic acid and 3-caffeoylquinic acid, is a water-soluble polyphenolic phenylacrylate compound produced by plants through the shikimic acid pathway during aerobic respiration. CGA is widely found in higher dicotyledonous plants, ferns, and many Chinese medicine plants, which enjoy the reputation of “plant gold.” We have summarized the biological activities of CGA, which are mainly shown as anti-oxidant, liver and kidney protection, anti-bacterial, anti-tumor, regulation of glucose metabolism and lipid metabolism, anti-inflammatory, protection of the nervous system, and action on blood vessels. We further determined the main applications of CGA in the food industry, including food additives, food storage, food composition modification, food packaging materials, functional food materials, and prebiotics. With a view to the theoretical improvement of CGA, biological activity mechanism, and subsequent development and utilization provide reference and scientific basis.